Ujaran Kebencian Dalam Al-Qur’an (Kajian Tafsir Tematik/Maudhû’i) - Muhammad Yahya; Kerwanto Kerwanto; Nurbaiti Nurbaiti (STIKes Ibnu Sina Ajibarang, 2023)
There are many negative impacts of hate speech such as inhibiting citizens in democracy, creating social polarization based on identity groups, and ultimately hostility, sowing the seeds of intolerance with the emergence of hardline groups. The purpose of this study is to find and explain hate speech perspective of the mufassir in the Qur'an, find and explain the solution of the Qur'an perspective of the mufassir in preventing and tackling hate speech. The method used in this study is qualitative (library research) by using content analysis and observation. Primary sources used are some of the products of interpretation of the famous mufasir, both from within the country and abroad. The secondary sources are books, journals, articles and websites that are closely related to hate speech and things that can prevent hate speech. The results of the study that the erm-term hate speech in the Qur'an that is considered relevant and representative of the theme, namely sakhiro, an-nabzu, sabba, hamaza, al-lamzu, al-ifku, namma and sihr and choose some verses from the trm-term, the authors found several components that are included in hate speech so that it can be formulated into a concept. The concept of hate speech includes: insults, defamation, unpleasant acts, provocations, and spreading false news. In addition, the author also found several ways and even solutions to prevent the emergence of hate speech behavior, namely: be careful with the provocative title of the site, look closely at the site address, fact-check the news, check the authenticity of news photos, and follow and anti-hoax discussion groups.